Challenges in Detecting Clinically Relevant Heparin-Induced Thrombocytopenia Antibodies - Warkentin, Theodore E. (Hämostaseologie, 2020)
Heparin-induced thrombocytopenia (HIT) is an antibody-mediated hypercoagulable state featuring high thrombosis risk and distinct pathogenesis involving immunoglobulin G-mediated platelet activation. The target of the immune response is a cationic “self” protein, platelet factor 4 (PF4), rendered antigenic by heparin. A key problem is that only a minority of anti-PF4/polyanion antibodies induced by heparin are pathogenic, i.e., capable of causing platelet activation and thereby clinical HIT. Since thrombocytopenia occurs frequently in hospitalized, heparin-treated patients, testing for “HIT antibodies” is common; thus, the problem of distinguishing between pathogenic and nonpathogenic antibodies is important. The central concept is that those antibodies that have platelet-activating properties demonstrable in vitro correlate well with pathogenicity, as shown by platelet activation tests such as the serotonin-release assay (SRA) and heparin-induced platelet activation assay. However, in most circumstances, immunoassays are used for first-line testing, and so it is important for clinicians to appreciate which immunoassay result profiles—in the appropriate clinical context—predict the presence of platelet-activating antibodies (Bayesian analysis). Clinicians with access to rapid, on-demand HIT immunoassays (e.g., particle gel immunoassay, latex immunoturbidimetric assay, chemiluminescent immunoassay) can look beyond simple dichotomous result interpretation (“negative”/“positive”) and incorporate semiquantitative interpretation, where, for example, a strong-positive immunoassay result (or even combination of two immunoassays) points to a greater probability of detecting platelet-activating antibodies, and hence supporting a diagnosis of HIT. Recent recognition of “SRA-negative HIT” has increased the importance of semiquantitative interpretation of immunoassays, given that strong immunoassay reactivity is a potential clue indicating possible HIT despite a (false) negative platelet activation assay.
Keywords: chemiluminescent immunoassay; heparin-induced thrombocytopenia; latex immunoturbidimetric assay; serotonin-release assay